2021
DOI: 10.47391/jpma.626
|View full text |Cite
|
Sign up to set email alerts
|

Perceived parenting styles and primary attachment styles of single and children living with both parents

Abstract: Objective: The study investigates the association between perceived primary parenting styles and attachment styles between single parent children and children living with both parents. Methods: A correlational research study was carried out on a sample of 200 children, 100single parent children (Boys=50; Girls=50) taken from single parent families living in child protection and welfare bureau and 100 children living with both parents (Boys=50; Girls=50) enrolled in different grades taken from a private school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…These studies point to how parent-child relationships influence the development of stress regulation throughout childhood, as well as through early adolescence. Parenting styles, while more distal, contribute to the quality of parental bonds and attachment, even in late adolescence and emerging adulthood [17,18,27]. Conceivably, parenting styles may have a lasting influence on offspring stress and other related factors throughout development.…”
Section: Attachment Parenting Style and Stress Response From A Develo...mentioning
confidence: 99%
“…These studies point to how parent-child relationships influence the development of stress regulation throughout childhood, as well as through early adolescence. Parenting styles, while more distal, contribute to the quality of parental bonds and attachment, even in late adolescence and emerging adulthood [17,18,27]. Conceivably, parenting styles may have a lasting influence on offspring stress and other related factors throughout development.…”
Section: Attachment Parenting Style and Stress Response From A Develo...mentioning
confidence: 99%
“…"Compared to children who lived with both parents, children of single parents had a more distant relationship with their parents and a perception of them as being authoritarian. While communication and trust work better within two parents' families [28]." They need to worry about their children's safety, physical problems, but also have to deal with economic and environmental pressures, so strict discipline and control becomes a more appropriate parenting style for them to maintain their authority.…”
Section: Mechanism 5: Female Independence Greatly Increases the Divor...mentioning
confidence: 99%
“…It has been shown that the parenting style approached in the relationship with a child can become their own parenting style in adult life [30]. Authoritarian parenting is associated with diminished communication skills, whereas authoritative parenting style leads to confidence in parenting skills, as well as effective parent-child communication [31]. The permissive parenting style can induce atypical behaviors in the child, but also generalized anxiety [32].…”
Section: The Importance Of Parenting Stylementioning
confidence: 99%